Utilization of 2,6-diaminopurine by Salmonella typhimurium. - Garber, B B (1980)
The pathway for the utilization of 2,6-diaminopurine (DAP) as an exogenous purine source in Salmonella typhimurium was examined. In strains able to use DAP as a purine source, mutant derivatives lacking either purine nucleoside phosphorylase or adenosine deaminase activity lost the ability to do so. The implied pathway of DAP utilization was via its conversion to DAP ribonucleoside by purine nucleoside phosphorylase, followed by deamination to guanosine by adenosine deaminase. Guanosine can then enter the established purine salvage pathways. In the course of defining this pathway, purine auxotrophs able to utilize DAP as sole purine source were isolated and partially characterized. These mutants fell into several classes, including (i) strains that only required an exogenous source of guanine nucleotides (e.g., guaA and guaB strains); (ii) strains that had a purF genetic lesion (i.e., were defective in alpha-5-phosphoribosyl 1-pyrophosphate amidotransferase activity); and (iii) strains that had constitutive levels of purine nucleoside phosphorylase. Selection among purine auxotrophs blocked in the de novo synthesis of inosine 5'-monophosphate, for efficient growth on DAP as sole source of purine nucleotides, readily yielded mutants which were defective in the regulation of their deoxyribonucleoside-catabolizing enzymes (e.g., deoR mutants).